Design and implementation of a crop health monitoring system - Kabir, Mashrur; Roy, Pranta; Labonnya, Sheikh Sabikun Naher; Hussain, Ashrar Ibne; Islam, Md. Ferdous (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.